2012
DOI: 10.18632/oncotarget.580
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of clinical data using human meiotic genes identifies a novel cohort of highly restricted cancer-specific marker genes

Abstract: Identifying cancer-specific biomarkers represents an ongoing challenge to the development of novel cancer diagnostic, prognostic and therapeutic strategies. Cancer/testis (CT) genes are an important gene family with expression tightly restricted to the testis in normal individuals but which can also be activated in cancers. Here we develop a pipeline to identify new CT genes. We analysed and validated expression profiles of human meiotic genes in normal and cancerous tissue followed by meta-analyses of clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(100 citation statements)
references
References 47 publications
3
96
0
1
Order By: Relevance
“…Recently, a novel cohort of CT genes was identified by meta-analyzing the expression profiles of human orthologs of mouse meiotic genes 19. This and other recent works8 support the proposal that a generalized hallmark of human tumors is a soma-to-germline transformation 9.…”
supporting
confidence: 55%
“…Recently, a novel cohort of CT genes was identified by meta-analyzing the expression profiles of human orthologs of mouse meiotic genes 19. This and other recent works8 support the proposal that a generalized hallmark of human tumors is a soma-to-germline transformation 9.…”
supporting
confidence: 55%
“…However, given that the normal function of many CT genes in spermatogenesis is unknown, it remained unclear whether proteins that normally specifically orchestrate meiotic chromosome segregation events (such as interhomolog association/recombination and sister centromere monopolarity) contribute to maintenance and/or development/progression of cancers. A screen for a subclass of CT genes that are specifically associated with mammalian meiotic spermatocytes revealed a few genes encoding functions associated with meiotic chromosome dynamics, such as the gene encoding the meiotic recombination hotspot activator PRDM9 and the meiosis-specific cohesin genes RAD21L1 and SMC1b (31,32). Meiotic chromosome regulator genes have been previously reported as CT genes (4-7), but only now is robust evidence starting to emerge to indicate that these so called meiCT (meiotic cancer testis) genes (a specific subgroup of the CT gene family) have an important influence on cancer chromosome biology.…”
Section: Activation Of Meiotic Functions In Cancer Cellsmentioning
confidence: 99%
“…Recent work in mice has demonstrated that the mammalian-specific gene Tex19.1 is required to promote normal levels of these meiotic recombination-initiating events (49). The human ortholog, TEX19, normally has expression restricted to the testis and embryo stem cells, but is also widely activated in cancer cells (31); importantly, this expression is required in a number of distinct cancer cell types to mediate proliferation and cancer stem-like cell self-renewal (50). While the mechanism of action of TEX19 in cancer cells remains unknown, this work further demonstrates the functional requirements for diverse meiotic chromosomal modulators, including regulators of meiotic recombination initiation, in oncogenesis.…”
Section: Activation Of Meiotic Functions In Cancer Cellsmentioning
confidence: 99%
“…с помощью технологии микрочипов, ни один из генов meiCT не показал достоверной гиперэкспрессии при КРР. Однако когда массивы данных были проанализированы по отдельности, некоторые гены показали значительное усиление экспрессии при КРР: NUT, CCDC105 и TCTE3 при сравнении опухолевой ткани с нормальной тканью толстой кишки [26].…”
Section: рис 2 экспрессия генов Ctage1b Magea1 и Kif2c в здоровых unclassified